Celebrity Endorsements, E-WOM, and Promotions Significantly Boost Youth Purchase Interest in Indonesia: Dukungan Selebriti, E-WOM, dan Promosi Secara Signifikan Meningkatkan Minat Beli Kaum Muda di Indonesia - Frmansah, Fiki; Komalasari, Dewi (Indonesian Journal of Law and Economics Review, 2024)
This study explores how celebrity endorsers, electronic word of mouth (E-WOM), and promotions affect consumer purchase interest, focusing on young consumers in Sidoarjo who buy Erigo products. Using a quantitative approach, data were gathered from 96 respondents aged 12 to 24 through purposive sampling and analyzed with SmartPLS. The results indicate that all three factors significantly and positively influence purchase interest. These findings suggest that integrating celebrity endorsements, fostering positive E-WOM, and designing effective promotions can enhance consumer interest and drive sales. Highlight: Celebrity endorsements significantly enhance product appeal among youth. Positive electronic word of mouth (E-WOM) boosts consumer interest. Effective promotional strategies drive higher purchase intentions. Keywoard: Purchase interest, celebrity endorsements, E-WOM, promotions, youth consumers